Montar uma ruína: Clube Alagoinha - Duarte, Lis Paim (2018)
From the moment its foundations were settle within the sea so that its facade could rest over the surface at a famous corner by the seafront, ALAGOAS YACHT CLUB (“Alagoinha”)’s presence stamped Ponta Verde and Pajuçara’s beaches encounter in such a remarkable way that, nowadays, its remains still hang over Maceió’s urban landscape both as a cultural icon and an undesirable wart. Bound together by the force of time, one cannot think about the city unless the already diluted shape of the ruins rising from the reefs comes to mind. The ancient beach club location is in fact the strongest and toughest beam of this architecture. As if in that exact point of Ocean and geography, and always through a degeneration process, a bigger narrative could be surprisingly agglutinated, erupting as a precise explosion amongst the wreckage… Formerly with a small team, later by myself, I kept visiting Alagoinha’s ruins every six months, in order to capture in film the fragments of such eruption. In parallel, I came across the rare photograph and VHS/ K7 tape registers owned by club’s founders, the Costa family, all of which were personally handed to me. My collection was then extended to more than 40 hours in video footages, 1800 photos, and about 20 hours in audio tapes fully recorded inside the ruins, including a number of ambient sounds plus testimonials by different narrators in a series of conversations with me. The (re)combination of all this material is what gives my own construction its particular form. MOUNTING A RUIN: ALAGOINHA CLUB proposes, therefore, an investigation on the poetics of montage that is performed in a double movement: on the one hand, it is a disclosure of the game proceedings involved in the creation and treatment of that archive inside and outside the camera, through the spaces of the very ruins, the mind, and the editing room/island; on the other, the montage operation itself is also that of the disruption of the possibility to create a linear narrative on the ongoing decline of Alagoinha, while its ruins are being targeted by transitory occupations and, especially after the announcement of a plan to build there a “touristic milestone”, by the imminent threat of disappearance as well. Unfolding the fragmented content of that precarious archive in a prime possible plot, and so connecting photographic, and descriptive, images, sonorous words, process reports, and distinct conversations, I get to experience the assembling of an authentic thesis-film (or would it be a film-thesis?).